Six walks in the fictional woods - Eco, Umberto (Charles Eliot Norton lectures ;, 1994)
"In Six Walks in the Fictional Woods Umberto Eco shares with us his Secret Life as a reader--his love for MAD magazine, for Scarlett O'Hara, for the nineteenth-century French novelist Nerval's Sylvie, for Little Red Riding Hood, Agatha Christie, Agent 007 and all his ladies. We see, hear, and feel Umberto Eco, the passionate reader who has gotten lost over and over again in the woods, loved it, and come back to tell the tale, The Tale of Tales. Eco tells us how fiction works, and he also tells us why we love fiction so much. This is no deconstructionist ripping the veil off the Wizard of Oz to reveal his paltry tricks, but the Wizard of Art himself inviting us to join him up at his level, the Sorcerer inviting us to become his apprentice."--